Accreditation as a tool for sustainable public acquisitions (Revista Direitos Humanos e Democracia, 2025)
The principle of sustainable development, which presupposes systemic integration between the economic, social and environmental dimensions, occupies a leading position in Law 14.133/2021, having been affirmed as a principle and objective of public procurement. The 1988 Federal Constitution establishes the holding of public tenders as a rule in the legal system, except for cases specified by law. In the meantime, Law 14.133/2021 provides for some auxiliary instruments for tenders and contracts, among which is accreditation, a horizontal procedure applicable to parallel and non-exclusive contracts; with third-party selection and in fluid markets. The article aims to analyze the efficiency of accreditation to enable sustainable contracts, in situations where accrediting more than one supplier presents itself as the most efficient way to meet the immediate need of the Public Administration and to implement the principle of sustainable national development. To this end, the article uses the decision of the Federal Court of Auditors in Ruling No. 351/2010, which recognizes a specific situation in which the use of accreditation proved to be more efficient in meeting the immediate and mediate needs of the Public Administration, when compared to the use of traditional bidding processes. Based on this, the article presents objective parameters that may be useful in identifying specific cases in which accreditation should be considered as a more advantageous option for contracting, as well as defending the need to assess, in the specific case, whether the use of accreditation may constitute a more efficient option than traditional bidding processes, provided that it is duly based on objective criteria and aligned with the primary public interest.
Keywords: Accreditation; Public Bidding; Public Contracting; Principle of Sustainable National Development; Efficiency; Federal Court of Auditors; Law 14,133/21